2005
DOI: 10.1080/07399330590917807
|View full text |Cite
|
Sign up to set email alerts
|

Coping Style and Women's Participation in Breast and Gynecological Screening

Abstract: The purpose of this project was to determine the role of coping style in women's practice of breast and gynecological screening behaviors. Women were classified into one of four coping groups based on measures of vigilance and screening distress. Data were analyzed from a subset of 85 U.S. women who participated in a larger longitudinal study designed to examine self-reported screening participation. Results indicate frequency of screening participation and importance of obtaining immediate mammography feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…We also showed that higher HADS scores were correlated with self-blame, behavioral disengagement, selfdistraction, use of emotional support, venting, denial, and less acceptance coping styles. Few studies have investigated the correlation between psychological distress and coping styles for breast cancer screening [29][30][31]. Unexpectedly, not only negative coping styles, for example self-blame, behavioral disengagement, denial, and less acceptance, but also positive coping styles, for example self-distraction and venting, were related to psychological distress.…”
Section: Discussionmentioning
confidence: 91%
“…We also showed that higher HADS scores were correlated with self-blame, behavioral disengagement, selfdistraction, use of emotional support, venting, denial, and less acceptance coping styles. Few studies have investigated the correlation between psychological distress and coping styles for breast cancer screening [29][30][31]. Unexpectedly, not only negative coping styles, for example self-blame, behavioral disengagement, denial, and less acceptance, but also positive coping styles, for example self-distraction and venting, were related to psychological distress.…”
Section: Discussionmentioning
confidence: 91%
“…The issues surrounding breast screening participation are most commonly researched by examining why women do not participate, rather than why they do (e.g., Johansson & Berterö, 2003;Speedy & Hase, 2000). Additionally, much research into breast screening participation focuses on psychological models of decision making (Barron et al, 2005;Siegler, Feaganes, & Rimer, 1995;Wardle & Pope, 1992). As a result of my research, I argue that women's decisions are invariably made in a social context that cannot be overlooked.…”
Section: Providing a Local Servicementioning
confidence: 94%
“…Participation in breast cancer screening is problematic, however, with most countries having difficulty in achieving a satisfactory participation rate. It has been claimed that, overall, fewer than 60% of women adhere to breast cancer screening guidelines (Barron, Foxhall, & Houfek, 2005).Confounding the issue of participation is the age at which screening should begin. The efficacy of breast cancer screening within the age group 40-49 years is a contentious issue from both a scientific and a public…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, researchers indicate the need to understand the importance of the combined role of cultural and emotional determinants for older Hispanic women in this process. Instead of examining cultural, emotional, and demographic determinants individually, researchers suggest that culture influences emotions, which has accounted for differences in cancer screening among NHW and Hispanic women (Arrendondo et al, 2008; Foxall, Barron, & Houfek, 2001; Barron, Foxall, & Houfek, 2005; Farmer, Reddick, D’Agostino, & Jackson 2007; Flynn, Betancourt, & Ormseth, 2011; Gao et al, 2009; Magai et al, 2007; Masterson, Hopenhayn, & Christian, 2010). If we examine these determinants in combination, we may gain a deeper understanding, which may inform interventions designed to reduce cancer screening disparities (Carillo et al, 2011).…”
Section: Purpose Of the Studymentioning
confidence: 99%